Palmitic Acid-Conjugated Radiopharmaceutical for Integrin αvβ3-Targeted Radionuclide Therapy - Guangjie Yang; Hannan Gao; Chuangwei Luo; Xiaoyu Zhao; Qi Luo; Jiyun Shi; Fan Wang (MDPI AG, 2022)
Peptide receptor radionuclide therapy (PRRT) is an emerging approach for patients with unresectable or metastatic tumors. Our previously optimized RGD peptide (3PRGD2) has excellent targeting specificity for a variety of integrin αvβ3/αvβ5-positive tumors and has been labeled with the therapeutic radionuclide [177Lu]LuCl3 for targeted radiotherapy of tumors. However, the rapid clearance of [177Lu]Lu-DOTA-3PRGD2 (177Lu-3PRGD2) in vivo requires two doses of 111 MBq/3 mCi to achieve effective tumor suppression, limiting its further clinical application. Albumin binders have been attached to drugs to facilitate binding to albumin in vivo to prolong the drug half-life in plasma and obtain long-term effects. In this study, we modified 3PRGD2 with albumin-binding palmitic acid (Palm-3PRGD2) and then radiolabeled Palm-3PRGD2 with 177Lu. [177Lu]Lu-DOTA-Palm-3PRGD2 (177Lu-Palm-3PRGD2) retained a specific binding affinity for integrin αvβ3/αvβ5, with an IC50 value of 5.13 ± 1.16 nM. Compared with 177Lu-3PRGD2, the 177Lu-Palm-3PRGD2 circulation time in blood was more than 6 times longer (slow half-life: 73.42 min versus 11.81 min), and the tumor uptake increased more than fivefold (21.34 ± 4.65 %IA/g and 4.11 ± 0.70 %IA/g at 12 h post-injection). Thus, the significant increase in tumor uptake and tumor retention resulted in enhanced efficacy of targeted radiotherapy, and tumor growth was completely inhibited by a single and relatively lowdose of 18.5 MBq/0.5 mCi. Thus, 177Lu-Palm-3PRGD2 shows great potential for clinical application.